2019
DOI: 10.1037/bne0000312
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and long-lasting cognitive consequences of adolescent chronic sleep restriction.

Abstract: Adolescence is a critical developmental period. An important change that occurs in adolescence is the neurological maturation for adult-type cognitive abilities. Research has linked adequate sleep quantity to successful learning and memory capabilities. However, due to a shift in sleep timing drive in adolescence, in combination with early awakening for school, the adolescent population is experiencing chronic sleep restriction (CSR). What repercussions to long-term memory capabilities could CSR in adolescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Central for studies of brain maintenance and brain reserve, is the idea that early life events may influence the onset of age-related cognitive decline (Jagust, 2016;Hohman and Kaczorowski, 2020). Therefore, it is important to consider the phases of life in which a behavior is measured or experimental manipulation applied (e.g., Asiminas et al, 2019;Howard and Hunter, 2019). What is considered young or old may vary by animal model and strain.…”
Section: When Does Cognition Decline?mentioning
confidence: 99%
“…Central for studies of brain maintenance and brain reserve, is the idea that early life events may influence the onset of age-related cognitive decline (Jagust, 2016;Hohman and Kaczorowski, 2020). Therefore, it is important to consider the phases of life in which a behavior is measured or experimental manipulation applied (e.g., Asiminas et al, 2019;Howard and Hunter, 2019). What is considered young or old may vary by animal model and strain.…”
Section: When Does Cognition Decline?mentioning
confidence: 99%
“…Using a classical object-place recognition (OPR) task in rats, the present study confirms that sleep, in comparison with post-encoding wakefulness, enhances the consolidation of hippocampus-dependent memory. Previous studies demonstrated a beneficial effect of sleep for OPR memory tested up to 24 h after learning (Bett et al, 2013;Binder et al, 2012;Howard & Hunter, 2019;Ishikawa, Yamada, Pavlides, & Ichitani, 2014;Oyanedel et al, 2014;Ozawa, Yamada, & Ichitani, 2011). By systematically varying the duration and depth of post-encoding sleep, the present study goes beyond those previous findings indicating that sleep can strengthen OPR memory such that it is even maintained over one week.…”
Section: Discussionmentioning
confidence: 42%
“…These results reveal that SD could deteriorate cognitive function in isoflurane-exposed mice by interfering with dCA1 neuronal activity and plasticity of dendritic spines. Available evidence have shown that both isoflurane exposure (Lin and Zuo, 2011;Liu et al, 2020) and SD (Howard and Hunter, 2019;Rajizadeh et al, 2020) can impair subsequent learning and short-time memory in adult rodents. Using the Y maze, we found that both isoflurane exposure and 24-h SD affected short-term memory in adult animals, which were in agreement with previous observations, and there was no significant difference between the two treatments.…”
Section: Discussionmentioning
confidence: 99%